Climate reconstruction for the last two millennia in central Iberia: The role of East Atlantic (EA), North Atlantic Oscillation (NAO) and their interplay over the Iberian Peninsula - Sánchez-López, Guiomar; Hernández, Armand; Pla-Rabes, S.; Trigo, Ricardo M.; Toro, M.; Granados, I.; Sáez, Alberto; Masqué, Pere; Pueyo Mur, Juan José; Rubio de Ingles, Maria Jesus; Giralt, Santiago (Quaternary Science Reviews, 2016)
A multi-proxy characterization of the uppermost sedimentary infill of an Iberian alpine lake (Cimera, 2140 m a.s.l.) was performed to establish the climatic and environmental conditions for the Iberian Central Range (ICR) over the last two millennia. This multi-proxy characterization was used to reconstruct the intense runoff events, lake productivity and soil erosion in the lake catchment and interpret these factors in terms of temperature and precipitation variability. The Roman Period (RP; 200 BCE – 500 CE) beginning was characterized by an alternation between cold and warm periods as indicated by short-lived oscillations of intense runoff conditions and soil erosion, although warm conditions dominated the end of the period and the Early Middle Age (EMA; 500–900 CE) onset in the ICR. A noticeable decrease in intense runoff events and a progressive decrease in soil erosion during the late EMA indicated a shift to colder temperatures. In terms of precipitation, both the RP and EMA climate periods displayed a transition from dry to wet conditions that led to a decrease in lake productivity. The Medieval Climate Anomaly (MCA; 900–1300 CE) was characterized by warm and dry conditions with frequent intense runoff episodes and increases in lake productivity and soil erosion, whereas the Little Ice Age (LIA; 1300–1850 CE) showed the opposite characteristics. The Industrial Era (1850–2012 CE) presented an increase in lake productivity that likely demonstrates the influence of global warming. The spatio-temporal integration of the Cimera record with other Iberian reconstructions has been used to identify the main climate drivers over this region. During the RP and EMA, N–S and E–W humidity gradients were dominant, whereas during the MCA and LIA, these gradients were not evident. These differences could be ascribed to interactions between the North Atlantic Oscillation (NAO) and East Atlantic (EA) phases. During the RP, the general warm conditions and the E–W humidity gradient indicate a dominant interplay between a ...